2014
DOI: 10.1002/btpr.2021
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering methods for the prevention of protein aggregation and improvement of product quality in a transient expression system

Abstract: in Wiley Online Library (wileyonlinelibrary.com) Mammalian expression systems are used routinely for the production of recombinant proteins as therapeutic molecules as well as research tools. Transient expression has become increasingly popular in recent years due to its rapid timeline and improvements in expression level. While improvements to transient expression systems have focused mainly on the level of protein expression, the aspect of protein quality has received little attention. The removal of unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Specifically, we tested genes encoding ER‐resident proteins widely reported to be involved in nascent polypeptide folding and assembly (BiP, PDI, and CypB), genes encoding activated forms of UPR transactivators (ATF6c and XBP1s) reported to generically increase the expression of ER chaperones/foldases (Dinnis and James, ), a potent small molecule inhibitor of PERK (GSK2606414, Harding et al, ) to inhibit eIF2α phosphorylation and lastly, chemical chaperones reported to alleviate deficient intracellular protein trafficking, minimize protein aggregation and relieve ER stress (e.g., Roth et al, ), specifically 4‐phenylbutyrate (PBA), dimethyl sulfoxide (DMSO), glycerol, betaine, and trimethylamine N‐oxide (TMAO). As it has been reported that the production of some DTE proteins can be improved by hypothermic culture temperatures (e.g., Estes et al, ), we also compared the effect of post‐transfection temperature shift to 32°C. For all transfections, recombinant Sp35Fc plasmid DNA load (3 μg) was kept constant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, we tested genes encoding ER‐resident proteins widely reported to be involved in nascent polypeptide folding and assembly (BiP, PDI, and CypB), genes encoding activated forms of UPR transactivators (ATF6c and XBP1s) reported to generically increase the expression of ER chaperones/foldases (Dinnis and James, ), a potent small molecule inhibitor of PERK (GSK2606414, Harding et al, ) to inhibit eIF2α phosphorylation and lastly, chemical chaperones reported to alleviate deficient intracellular protein trafficking, minimize protein aggregation and relieve ER stress (e.g., Roth et al, ), specifically 4‐phenylbutyrate (PBA), dimethyl sulfoxide (DMSO), glycerol, betaine, and trimethylamine N‐oxide (TMAO). As it has been reported that the production of some DTE proteins can be improved by hypothermic culture temperatures (e.g., Estes et al, ), we also compared the effect of post‐transfection temperature shift to 32°C. For all transfections, recombinant Sp35Fc plasmid DNA load (3 μg) was kept constant.…”
Section: Resultsmentioning
confidence: 99%
“…TGE methods can be employed to fast‐track the production of multiple biologics to perform biophysical analyses and early preclinical evaluation of drug candidates. Furthermore, transient production is increasingly being employed to evaluate product manufacturability and refine process conditions (Estes et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High rates of production may swamp the post-translational modification apparatus leading to heterogeneous product formation or in cellulo aggregation, like Russell bodies (Hasegawa, Woods, Kinderman, He, & Lim, 2014). Some of these problems may be ameliorated by codon optimization, by stuffer DNA, by choosing a 'weaker' promoter, or by engineering cells to have enhanced properties (B. Estes et al, 2015;Rajendra et al, 2012).…”
Section: Of 28mentioning
confidence: 99%
“…Limitations in the secretion of recombinant proteins can impact both protein quality and yield, which can have a negative impact on downstream processes. Published reports have focused on the characterization of such ‘difficult‐to‐express’ recombinant proteins and described the modification of culture conditions 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or the design of appropriate cell/protein engineering strategies to overcome restrictions in their production 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26. However, little is known regarding the mechanisms underpinning poor recombinant protein production, particularly between proteins of high sequence similarity.…”
mentioning
confidence: 99%